2011
DOI: 10.1016/j.jedc.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Labor market institutions and inflation volatility in the euro area

Abstract: a b s t r a c tDespite having had the same currency for many years, EMU countries still have quite different inflation dynamics. In this paper we explore one possible reason: country specific labor market institutions, giving rise to different inflation volatilities. When unemployment insurance schemes differ, as they do in EMU, reservation wages react differently in each country to area-wide shocks. This implies that real marginal costs and inflation also react differently. We report evidence for EMU countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 40 publications
2
58
0
Order By: Relevance
“…The probability of filling a vacancy q is typically set between 0.7 (den Haan, Ramey, and Watson (2000) and Krause and Lubik (2007)) and 0.9 (Andolfatto (1996) and Hairault (2002)). We choose the lower bound of values used in the literature, since a lower probability seems more in line with the European case (see Campolmi and Faia (2011)). …”
Section: Labour Marketmentioning
confidence: 99%
“…The probability of filling a vacancy q is typically set between 0.7 (den Haan, Ramey, and Watson (2000) and Krause and Lubik (2007)) and 0.9 (Andolfatto (1996) and Hairault (2002)). We choose the lower bound of values used in the literature, since a lower probability seems more in line with the European case (see Campolmi and Faia (2011)). …”
Section: Labour Marketmentioning
confidence: 99%
“…Likewise, it has been shown that labor market institutions matter for the adjustment of wages and job flows to external shocks [9]. The main channel is the one highlighted so far.…”
Section: Exchange Rate Fluctuationsmentioning
confidence: 86%
“…All countries are exposed to the same worldwide external shocks. However, since they have different labor market institutions they react differently to the same external shock [9]. Since the European Central Bank decides on a common monetary policy, the question arises as to whether it should take into account those differences across countries and how they affect the various countries' responses to external shocks.…”
Section: Exchange Rate Effects Within a Currency Areamentioning
confidence: 99%
See 1 more Smart Citation
“…However, open economy models rarely feature search and matching frictions in the labour market. Hairault (2002) and Campolmi and Faia (2011) …”
mentioning
confidence: 99%